Users' Satisfaction as a Valid Measure for Information Resources: A Case of Public Libraries - Bashir, Faiza, Soroya ,Saira Hanif; and Khanum, Almas (Journal of Library Administration, 2018)
The mission of public libraries is to serve the unique needs of their local communities. Public library User's play a very vital role in the development of these libraries by suggesting or recommending additions to the collection. This study aims to evaluate the satisfaction of users with the quality and quantity of library collection. A self structured questionnaire based on open and close ended question was constructed. A purposive sample of one hundred users was selected. The data were qualitatively analyzed using a thematic approach. Positive opinion observed related to the library response towards the suggested titles. Almost half the population of respondents was satisfied with the availability of their suggested titles in library. Most of them were dissatisfied regarding the maintenance of equal collection of books and they are not encouraged by the library staff during the books suggestion process. It concludes that there is a need to evaluate the existing library collections.
Keywords: dept.ils; information quality; information resources; public libraries; user satisfaction

Emerging Trends of Acquisition in Public Libraries of Pakistan: Challenges and Issues - Bashir, Faiza; Hanif Soroya, ,Saira; Soroya, M. Shahid; Khanum, Almas (Library Collections, Acquisitions, & Technical Services, 2015)
Acquiring material in public libraries is a core library activity to fulfill the unique needs of the reader's community. The present study aims to explore the trends of monograph acquisition in public libraries. The population consists of the four major public libraries of Lahore. A case study approach has been used to achieve the objectives of the study. Research is based on primarily the personal visits of the researcher to the acquisition departments of these libraries in order to collect data. Structured interviews were carried out with acquisition librarians to investigate the process of purchasing. The analysis of data reveals that a high ratio of Urdu language books has been purchased during the last decade, literature and religion being the major purchase area, whereas, art and architecture, pure sciences, and languages are the most neglected. The findings further revealed that the studied libraries have primarily been using traditional and informal techniques for acquiring material.
Keywords: Pakistan librarianship; acquisition trends; dept.ils; monograph acquisition; public libraries